Gambaran Nyeri Punggung Bawah pada Ibu Hamil Trimester III - Kurniati Devi Purnamasari; Melyana Nurul Widyawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to describe low back pain in third trimester pregnant women. The method used is a cross sectional descriptive study design. The results of the study, respondents who experienced mild pain as much as 20%, 50% experienced moderate pain and as many as 30% experienced severe pain accompanied by accompanying symptoms. Although it is a problem, 82% of adolescents only let go when pain arises or only drink warm water and press on the affected part (18%). Third trimester pregnant women seek help from their husbands and families (87.2%) regarding problems that arise and only, 12.8% of third trimester pregnant women seek help from health workers / midwives. In conclusion, most respondents have experienced low back muscle pain. Generally, information about the lower back is mostly obtained from other pregnant women and parents. When experiencing low back most pregnant women ask for help from their husbands and families. Keywords: Trimester III Pregnant Women, Lower Back Pain